UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUNMANGKOKAN (Polyscias scutellaria) TERHADAP BAKTERI Propionibacterium acnes - Siti Nurbaya; Dicky Yuswardi Wiratma; Elly Sitorus; Amaliah Insani (Jurnal Farmanesia, 2021)
Indonesia is a tropical country that has a variety of plants, one of which is the succulent plant (Polyscias Scutellaria). Mangkukan plant contains flavonoid compounds, alkaloids, saponins, polyphenols, fats. This study aimed to determine the antibacterial activity of the ethanol extract of the leaves of the Mangkokan (Polyscias Scutellaria) against Propionibacterium acnes bacteria. The tests were carried out through the stages of collecting materials, preparing simplicia, making an ethanolic extract of Mangkukan leaves, and testing the inhibitory power of basil leaves against Propionibacterium acnes bacteria. The manufacture of ethanolic extract of the leaves of the Mangkokan was carried out by the maceration method using 96% ethanol. Antibacterial activity testing was carried out using the agar diffusion method using disc paper. The results of the study based on the results of phytochemical screening showed that the simplicia and ethanol extract of the Mangkukan leaf contained alkaloids, flavonoids, glycosides, tannins, saponins, steroids/triterpenes. Meanwhile, the results of the antibacterial activity test of the ethanolic extract of the Mangkokan leaf have antibacterial properties against Propionibacterium acnes at extract concentrations of 30% (6.74 mm), .35% (6.84 mm), 40% (7.26 mm), 45% (7.32 mm), 50% (8.68 mm) with medium resistance zone. The positive control used 30 g chloramphenicol disc paper with an inhibition zone diameter of 21.89 and the negative control used 10% DMSO solution which had no inhibition zone. The ethanol extract of basil leaves has antibacterial activity against Propionibacterium acnes bacteria.